Risk of Malignancy in a Nationwide Cohort of Elderly Inflammatory Bowel Disease Patients - Khan, Nabeel (Drugs Aging, 2017)
BACKGROUND: Management of elderly inflammatory bowel disease (IBD) patients (≥ 65 years of age) is complicated due to many factors, including a higher risk of cancer, which may impact therapeutic decisions. OBJECTIVE: The aim of this study was to determine the risk of cancer among elderly IBD patients compared with younger IBD patients. Additionally, the absolute risk of malignancy and factors contributing to it were evaluated, and therapeutic patterns among the elderly were assessed. METHODS: This retrospective cohort study extracted data from the Truven Health Analytics MarketScan(®) database. Among adult IBD patients who were free of cancer before starting on corticosteroids, immunomodulators, or biologics, a Cox model for time to cancer was fitted that adjusted for several covariates, including time-dependent treatment. Baseline results were evaluated by age group, as were the incidence of cancer and the distribution of cancer subtypes. RESULTS: The elderly IBD cohort (n = 8788) had a higher prevalence of cancer and several other ailments before starting treatment, relative to the younger IBD cohort aged 18–64 years (n = 54,971). During follow-up, the elderly IBD cohort experienced a higher incidence of malignancy, confirmed by a hazard ratio (HR) of 3.04 (95% confidence interval [CI] 2.71–3.41) from the Cox model fit. The risk of cancer was also significantly associated with male sex (HR 0.82 female), duration of disease (HR 1.08), several comorbidities and corticosteroid use (HR 1.35), but not with the use of immunomodulators or biologics. Non-Hodgkin’s lymphoma, urinary tract malignancy, and prostate, lung, and female breast cancers were observed more commonly in this elderly IBD cohort when compared with the same age group in the Surveillance, Epidemiology, and End Results (SEER) database. CONCLUSIONS: The elderly with IBD have a higher risk of malignancy when compared with younger IBD patients and the general age-matched population, with certain cancers being more common among these patients.